ETA: Robust software for determination of cell specific rates from extracellular time courses. (21st January 2013) - Murphy, Taylor A.; Young, Jamey D.
Abstract Accurate quantification of cell specific rates and their uncertainties is of critical importance for assessing metabolic phenotypes of cultured cells. We applied two different methods of regression and error analysis to estimate specific metabolic rates from time‐course measurements obtained in exponentially growing cell cultures. Using simulated data sets to compute specific rates of growth, glucose uptake, and lactate excretion, we found that Gaussian error propagation from prime variables to the final calculated rates was the most accurate method for estimating parameter uncertainty. We incorporated this method into a MATLAB‐based software package called Extracellular Time‐Course Analysis (ETA), which automates the analysis workflow required to (i) compute cell specific metabolic rates and their uncertainties; (ii) test the goodness‐of‐fit of the experimental data to the regression model; and (iii) rapidly compare the results across multiple experiments. ETA was used to estimate the uptake or excretion rate of glucose, lactate, and 18 different amino acids in a B‐cell model of c‐Myc‐driven cancer. We found that P493‐6 cells with High Myc expression increased their specific uptake of glutamine, arginine, serine, lysine, and branched‐chain amino acids by two‐ to threefold in comparison to low Myc cells, but exhibited only modest increases in glucose uptake and lactate excretion. By making the ETA software package freely available to the scientific community, we expect that it will become an important tool for rigorous estimation of specific rates required for metabolic flux analysis and other quantitative metabolic studies. Biotechnol. Bioeng. 2013; 110: 1748–1758. © 2013 Wiley Periodicals, Inc.